2002
DOI: 10.1067/mva.2002.123332
|View full text |Cite
|
Sign up to set email alerts
|

Rat and human aortic smooth muscle cells display differing migration and matrix metalloproteinase activities in response to dexamethasone

Abstract: Dexamethasone inhibits rat aortic smooth muscle cell migration, MMP-2 activity, and MMP-2 secretion and increases TIMP-2 secretion. These effects are not observed in human aortic smooth muscle cells. These findings may explain why dexamethasone inhibits neointimal hyperplasia in animal models but is ineffective in humans. Inhibition of human smooth muscle cell migration in vitro may be useful in predicting the effectiveness of future therapeutic agents for treatment of neointimal hyperplasia in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
11
2
Order By: Relevance
“…These results are different from those reported by Bohlen et al They demonstrated that leptin inhibited proliferation of cultured human aortic smooth muscle cell and downregulated the short isoforms significantly, whereas the long isoforms were not influenced [18]. Data from experiments with rodent cells may differ from those with human ones, which is a possible explanation for the differences between their work and our current study [19]. However, there exit other possibilities.…”
Section: Discussioncontrasting
confidence: 56%
“…These results are different from those reported by Bohlen et al They demonstrated that leptin inhibited proliferation of cultured human aortic smooth muscle cell and downregulated the short isoforms significantly, whereas the long isoforms were not influenced [18]. Data from experiments with rodent cells may differ from those with human ones, which is a possible explanation for the differences between their work and our current study [19]. However, there exit other possibilities.…”
Section: Discussioncontrasting
confidence: 56%
“…It is also important to recognize that ␤-adrenergic agonists have both PKAdependent and -independent effects on actin depolymerization in airway smooth muscle and, therefore, PKA may not mediate all the effects that ␤-adrenergic agonists have on actin remodeling (29). Finally, even less is known about the mechanisms, probably multiple, that underlie the inhibitory effects of glucocorticoids on migration (30). However, given the evidence that p38 MAPK has a major role in regulating migration in ASMCs, it is interesting that, in HeLa cells, glucocorticoids did inhibit p38 MAPK signaling by inducing a sustained expression of MAPK phosphatase 1 (MKP-1) (31).…”
Section: Inhibition Of Asmc Migrationmentioning
confidence: 97%
“…In vitro, dexamethasone has been shown to downregulate DNA synthesis, proliferation and chemotactic activity of human fetal lung fibroblasts in a dose-dependent fashion [30] . Dexamethasone further directly inhibits thrombin-stimulated proliferation of human airway smooth muscle cells [31] as well as proliferation, DNA synthesis [32] and migration of rat and human aortic smooth muscle cells in culture conditions [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) inhibits smooth muscle cell migration and activity of MMP-2, one of the zinc-dependent metalloproteases, which has been specifically implicated in smooth muscle cell migration. Dexamethasone was recently shown to inhibit in vitro production and activity of MMP-2 both directly as well as through enhancing NO production [13,14] .…”
Section: Introductionmentioning
confidence: 99%